2023
DOI: 10.3390/cells12182261
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale CAR Organization at the Immune Synapse Correlates with CAR-T Effector Functions

Julia Sajman,
Oren Yakovian,
Naamit Unger Deshet
et al.

Abstract: T cells expressing chimeric antigen receptors (CARs) are at the forefront of clinical treatment of cancers. Still, the nanoscale organization of CARs at the interface of CAR-Ts with target cells, which is essential for TCR-mediated T cell activation, remains poorly understood. Here, we studied the nanoscale organization of CARs targeting CD138 proteoglycans in such fixed and live interfaces, generated optimally for single-molecule localization microscopy. CARs showed significant self-association in nanocluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The CAR-T to tumor interaction encompasses a CAR immune synapse, wherein the initial contact between T cell and tumor is stabilised by the CAR antibody to target antigen binding interaction, which develops into a cluster of engaged CAR constructs 25,26 . Although the biophysical properties of the CAR-T to antigen synapse are not as well characterized as native TCR immune synapses, it is likely that the strength of this interaction as well as the number of target antigens will determine whether the synapse becomes functional; i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CAR-T to tumor interaction encompasses a CAR immune synapse, wherein the initial contact between T cell and tumor is stabilised by the CAR antibody to target antigen binding interaction, which develops into a cluster of engaged CAR constructs 25,26 . Although the biophysical properties of the CAR-T to antigen synapse are not as well characterized as native TCR immune synapses, it is likely that the strength of this interaction as well as the number of target antigens will determine whether the synapse becomes functional; i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although the biophysical properties of the CAR-T to antigen synapse are not as well characterized as native TCR immune synapses, it is likely that the strength of this interaction as well as the number of target antigens will determine whether the synapse becomes functional; i.e. triggers death of the target cell through release of cytolytic granules concomitant with T cell signalling to promote proliferation and cytokine secretion 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CD138 has recently emerged as a potentially identifying feature of WM tumor cells, associated with IgM peaks and MYD88 mutations ( 378 ). Recent research has shown the role of nanoscale organization of CARs and TCRs for CAR-T cells targeting CD138 with yet unknown consequences ( 379 ). Future investigations can determine whether these structures are suitable targets for CAR-T-cell therapy in WM.…”
Section: Waldenström’s Macroglobulinemiamentioning
confidence: 99%